NaCl effect on germination and seedling fresh weight of Stenocereus eruca (Brandegee) A.C. Gibson & K.E. Horak - Beltrán-Morales, F. Alfredo; Arce-Amezquita, Pablo Misael; Ruiz-Espinoza, Francisco Higinio; Beltrán-Valdivia, Valeria; Hernández-Montiel, Luis Guillermo; Murillo-Amador, Bernardo (Journal of the Professional Association for Cactus Development, 2021)
Environmental disruption is particularly determinant for cacti development since they have slow growth and long life cycles. Soil and water salinity are two of the main environmental factors that are considered primordial for the propagation, seedling growth, establishment, and development of coastal cacti. The objective of this study was to evaluate chirinola (Stenocereus eruca) seed germination and seedling fresh weight using NaCl as a saline medium. One hundred seeds divided into five replicates of 20 seeds in a completely randomized design, were treated with five salinity levels and distilled water as control (0, 2, 6, 8, and 10 dS m-1). Seeds were picked up from ripe fruits at a wild Stenocereus eruca population near San Carlos, Baja California Sur, México. Seedling fresh weight was significantly affected by saline stress, with lower fresh weight at the highest doses of 10 dS m-1, and the greatest fresh weight production was obtained with 0 and 2 dS m-1. However, germination percentage was greater at intermediate levels of 2 and 4 dS m-1 and lowest at 10 dS m-1 using NaCl; however, more studies should be conducted including other growth variables, seed viability, and salinity levels.